Oracle CRM on demand combined analyses - Lairson, Michael D. (Osborne ORACLE Press., 2011)
"From Oracle Press--a detailed, step-by-step guide to using combined analyses to develop reports within Oracle CRM On DemandWritten by a renowned expert on the topic, Oracle CRM On Demand Combined Analyses provides a detailed and methodical explanation of how and when to use combined analyses within Oracle CRM On Demand. Combined analyses provide a mechanism by which outer joins between tables can be created virtually. This is unique to the CRM On Demand environment, and this book explains the process in detail. This Oracle Press guide describes the mechanics of creating a combined analysis, while highlighting real-world business cases where a combined analysis is critical to developing an accurate and meaningful report. These case studies for different types of report unions provide a framework for tested and proven usage of the set operators in developing combined reports. Oracle CRM On Demand Combined Analyses is written by recognized Oracle CRM On Demand expert who has developed training courses for Oracle Covers a largely undocumented topic area Features real-world case studies throughout includes coverage of: Combined Analyses Basics; Negative (Null) Reporting; Layout Considerations; Result Columns; Filtering Combined Analyses"--